All together now: Cellular and molecular aspects of leaf development in lycophytes, ferns, and seed plants - Romanova, Marina A.; Domashkina, Valentina V.; Maksimova, Anastasiia I.; Pawlowski, Katharina; Voitsekhovskaja, Olga V. (Frontiers in Ecology and Evolution, 2023)
Recent advances in plant developmental genetics together with rapid accumulation of transcriptomic data on plants from divergent lineages provide an exciting opportunity to explore the evolution of plant morphology. To understand leaf origin in sporophytes of land plants, we have combined the available molecular and structural data on development of leaves with different morphologies in different plant lineages: clubmosses, spikemosses, leptosporangiate ferns, ophioglossioid ferns, marattioid ferns, whisk ferns, horsetails, and conifers. Specifically, we address the peculiarities of proximo-distal, ad/abaxial, and lateral development; presence/absence of mesophyll differentiation into palisade and spongy parenchyma; and type of leaf vascular bundles (collateral and bicollateral). Furthermore, taxon-specific and morphology-specific features of leaf development are considered in the context of the organization of shoot apical meristems (SAMs)—monoplex, simplex, or duplex—that produce leaf primordia. The data available imply that cellular patterns of leaf initiation correlate strongly with the structure of the SAMs but not with further leaf development or morphology. The later stages of leaf development are neither correlated with SAM structure nor with taxonomy. Occurrence and, if available, patterns of expression of homologs of the angiosperm genes responsible for the development of adaxial (ARP and C3HDZ) and abaxial (YABBY and KANADI) leaf domains, or establishment of the leaf marginal meristem (WOX) are discussed. We show that there is no correlation in the set of homologs of TFs that regulate abaxial and adaxial leaf domain development between leaves containing only spongy and no palisade mesophyll (of spikemosses, clubmosses, whisk ferns, horsetails, and most conifers), and leaves differentiated into palisade and spongy mesophyll (of leptosporangiate ferns, Ginkgo, Gnetum, and angiosperms). Expression of three out of four regulators of leaf development in primordia of both leaves and sporangia—C3HDZ in spikemosses and whisk ferns, YABBY in clubmosses and KANADI in spikemosses and horsetails—indicates that a sporangium developmental program could have been co-opted as a “precursor program” for the origin of microphylls and euphylls. Additionally, expression of leaf development regulators in SAMs of spikemosses (ARP, C3HDZ, and KANADI), clubmosses (YABBY), leptosporangiate ferns (C3HDZ), and horsetails (C3HDZ and KANADI) indicates that at least some mechanisms of SAM regulation were co-opted as well in the pre-program of leaf precursors.